The impact of the quality of integrated reporting disclosure on corporate reputation / Mira Susanti Amirrudin, Mazni Abdullah and Zakiah Saleh - Amirrudin, Mira Susanti; Abdullah, Mazni; Saleh, Zakiah (Universiti Teknologi MARA, 2021)
In 2013, the International Integrated Reporting Council (IIRC) issued the Integrated Reporting (IR) Framework to improve corporate reporting. The purpose of IR is to integrate financial and non-financial information to explain how the organisation creates value and improves firm performance over time. Since the introduction of IR, a company weighs the benefits over the costs of changing to IR. Recent trends in IR have heightened the need to examine the actual contents of IR. The objective of this study was to find the relationship between preparing a high-quality IR and corporate reputation. Corporate reputation is one of the main objectives for the preparation of IR, and preparing a high-quality IR can positively impact corporate reputation. Data was collected from a sample of 120 companies from the IIRC websites for three years (360 firm-year observations) to examine the quality of following the 2013 Framework. An index was developed, and the corporate reputation score was collected from the RepTrak websites. The finding showed that companies preparing high-quality IR reports had a significant positive relationship with corporate reputation. Preparing a highquality IR sends a signal to users of annual reports as a connotation of the company (good product or services, ethical management reporting), which will help build trust towards the company and improve its reputation. This study contributes by providing empirical evidence for a company, which is uncertain about the benefits of IR. The IR disclosure score can be used as a reference by IIRC and policymakers to prepare the IR.